2015
DOI: 10.1039/c5cp02096d
|View full text |Cite
|
Sign up to set email alerts
|

Tandem deprotonation/azide–tetrazole tautomerization of 4,6-diazido-N-nitro-1,3,5-triazin-2-amine in dimethylsulfoxide solutions: a theoretical study

Abstract: 4,6-Diazido-N-nitro-1,3,5-triazin-2-amine (2) is a new promising high-energy organic compound that isomerizes in dimethylsulfoxide (DMSO) solutions to form unknown products with interesting 13C and 15N NMR spectroscopic characteristics. To identify these products, the relative energies and the 13C and 15N chemical shifts were calculated for various prototropic and valence isomers of 2. It was found that this diazide in DMSO solutions exists in equilibrium with the deprotonated form of 5-azido-N-nitrotetrazolo[… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…These sets can be differentiated by the signal intensity that increases in the order N α < N γ < N β . It has been shown that the GIAO‐TPSSh/M06‐2X calculations allow one to correctly assign the signals in each of the three sets even when the differences in the chemical shifts of the signals are smaller than the overall MAD between the experimental and calculated δ N values. The correct assignment is possible owing to the fact that the calculation errors of δ N values for a given type of the azido group atoms (N α , N β or N γ ) are mostly systematic; in the case of (hetero)aromatic azides, the systematic error varies with the nature of the (hetero)aromatic core.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These sets can be differentiated by the signal intensity that increases in the order N α < N γ < N β . It has been shown that the GIAO‐TPSSh/M06‐2X calculations allow one to correctly assign the signals in each of the three sets even when the differences in the chemical shifts of the signals are smaller than the overall MAD between the experimental and calculated δ N values. The correct assignment is possible owing to the fact that the calculation errors of δ N values for a given type of the azido group atoms (N α , N β or N γ ) are mostly systematic; in the case of (hetero)aromatic azides, the systematic error varies with the nature of the (hetero)aromatic core.…”
Section: Resultsmentioning
confidence: 99%
“…These sets can be differentiated by the signal intensity that increases in the order N α < N γ < N β . [31] It has been shown [6,7] that the GIAO-TPSSh/M06-2X calculations allow one to correctly assign the signals in each of…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations